Mediastinal high-grade vasculogenic mesenchymal tumour with seminoma: a case report and literature review - Shang Zhanxian; Han Yuchen; Wei Jinzhi; Zhu Lei (BMC, 2023)
Abstract Germ cell tumours with somatic-type solid malignancy (GCT-STM) are a rare disease of the mediastinum. Recently, a cohort of vasculogenic mesenchymal tumour (VMT)-nonseminoma cases with different prognoses were recognized and reported. Here, we report a case of mediastinal high-grade VMT with a seminoma. A 16-year-old male had a fever, chest tightness and fatigue. Chest CT showed a 7.5 cm×5.3 cm solid mass in the right anterior mediastinum. The serum levels of alpha-fetoprotein (AFP), beta-human chorionic gonadotropin (β-HCG) and carcinoembryonic antigen (CEA) were within the normal range. Tumorectomy was performed. The tumour was irregular, and no capsule was found. The cut surface was greyish white and greyish brown with medium consistency. There were foci of bleeding and necrosis. Microscopic histology showed prominent vascular proliferation, which was lined by mildly atypical endothelial cells in a cellular stroma with significant cytologic atypia. The vascular spectrum varied from crevice-like or antler-like thin- to thick-walled vessels. Beyond the tumour area, inside the remnant thymus tissues, there were small clusters of polygonal tumour cells with clear cytoplasm, distinct cell membranes, and round to polygonal nuclei with prominent nucleoli that were positive for Oct4, PLAP, SALL4 and CD117. The patient did not receive any treatments pre- or postoperation, and his condition was stable without progression after 14 months of follow-up evaluation. Here, we added a new entity of GCT-STM of the mediastinum composed of VMT and seminoma. A better understanding of the pathological features of GCT-VMT could help pathologists improve their awareness of these rare diseases.